Biotechnology for Sustainable Materials - Bhatia, Dr Shashi; Garbero, Roberto; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Biotechnology for Sustainable Materials is an open access, peer-reviewed journal featuring all aspects of biotechnology aimed at the production of sustainable and renewable materials. Sustainable materials are meant as materials derived from renewable, recycled and waste carbon resources and their combinations, which at the end of life can be recycled, biodegraded or composted. The vision for Biotechnology for Sustainable Materials is to contribute to the advancement of circular bioeconomy for materials and sustainable production. The main topics in scope are, but not only limited to: Plant- and microbe-based biopolymers and materials Bioplastics production, degradation and composting Biomaterials blend, composites, and fabricated materials for biotechnological applications Biomolecules for sensing Sustainable biomaterials for food and packaging Biobased materials for CO2 capture and energy storage Next generation biomaterials Chemically recyclable materials Materials that can be upcycled, repurposed, and reprocessed through sustainable bioprocesses Construction biomaterials Biomaterials for clothing Biomaterials for cosmetics Biomaterials for drug delivery and biomedical applications Experimentation, rational design for synthesis and processing Aspects of recycling, safety, and techno-economic analysis Policy issues, life cycle assessments, and debates A key aim of Biotechnology for Sustainable Materials is to promote the visibility and reach of valid, diverse, and innovative research. While the main focus remains on research and reviews of wide applicability and relevance, the journal is also open to consider confirmatory research, short communications, data analyses and discussions, local studies of interest for specific regions, and case studies where the authors are able to show meaningful relevance to the broader discussion around key topics in environmental biotechnology. Biotechnology for Sustainable Materials aims to highlight innovations that promote sustainable cities and communities, responsible consumption and production, life below water and life on land, according to the Sustainable Development Goals framework. Furthermore, the scope and the research published in Biotechnology for Sustainable Materials aim to resonate with the principles of Green Chemistry, particularly with the focus on safer solvents and reactions, energy efficiency, renewable feedstocks, degradation after use, and avoidance of chemical derivatives. .
Keywords: Biotechnology; Chemistry, Technical; Polymers; Biomaterials; Industrial microbiology; Plant biotechnology; Biotechnology; Industrial Chemistry; Polymers; Biomaterials; Industrial Microbiology; Plant Biotechnology